CRISPR/Cas9-Induced mutations of chNHE1 gene in chicken primordial germ cells - Hanh, Nguyen Van; Trong, Nguyen Dinh; Hong , Nguyen Thi; Linh, Chu Khanh; Ha, Chu Hoang; Phat , Do Tien (Vietnam Journal of Biotechnology, 2024)
In recent years, CRISPR/Cas9 technology has been extensively applied in gene editing research across plants as well as animal subjects, making it an effective tool in aiding the investigation of interactions between pathogens and hosts. Avian leukosis virus subgroup J (ALV-J) is the first known virus-related tumor disease causing avian leukosis, which can lead to major economic losses due to decreased productivity and increased mortality in infected chicken flocks. This poses a significant threat to the poultry industry worldwide, including Vietnam, as ALV-J is considered one of the most difficult pathogens to control. ALV-J infects the host cells by the meditation of the chicken NA+/H+ exchange type 1 (chNHE1) receptor. In this study, a CRISPR/Cas9 construct was developed and successfully delivered into the primordial germ cells of H’Mong-Vietnamese chickens. The insertion and expression of the transgenes in chicken cells were demonstrated by GFP expression and PCR with specific primers. The CRISPR/Cas9 induced mutations in the target gene chNHE1 were identified and characterized via ICE analysis (Synthego). The knockout score was indicated at 23 points from one of three tested cell batches. Various induced mutations were observed at the target locations, indicating the presence of different mutant cell lines in the tested cell batch. This is the first success in utilizing the CRISPR/Cas9 system to induce targeted mutations of the chNHE1 gene in the primordial germ cells of a local chicken variety in Vietnam. Our results provide a potential approach for further research to enhance the poultry health and productivity of local livestock.